A high-performance vernier permanent-magnet machine for aerospace application - Malaiyan Karthikeyan Srihariharan (Nanyang Technological University, 2023)
The more-electric aircraft initiative is a significant technological advancement in the aviation sector, with the goal of reducing fuel consumption and move towards green energy. Electrically powered actuators play an important role in the electrification of the aviation sector. This is achieved by replacing traditional hydraulic systems with electrically powered actuators. Electrical machines are a crucial component of the actuation system. Extensive research on permanent magnet synchronous motors in recent years, both in aerospace and automotive industry makes it the preferred choice. Recent research advancements in vernier permanent magnet machines for electric vehicles have shown promising results. In these applications, vernier permanent magnet machines have the potential to decrease the necessity for a gearbox to some degree. Consequently, from a system efficiency perspective, the use of vernier permanent magnet machines is appropriate for the actuation system. Hence, this work focuses on evaluating the feasibility of using a vernier permanent magnet motor for aerospace applications. Simulations using Finite Element Analysis (FEA) are utilized to evaluate the designed dual stator vernier permanent magnet machine against the benchmarked parameters for electrical actuation system’s motor.